BIBLICAL AND THEOLOGICAL FOUNDATIONS OF FORMATION JESUS’ DISCIPLE - Naibaho, Yanti Vidarosa; Donobakti, Yohanes Anjar; Naibaho, Megawati; Lay, Sergius (LOGOS, 2025)
Jesus as Master can be seen all through the New Testament. The heart of Jesus is the mission entrusted to Jesus by his Father. In this sense, those who want to follow Jesus’s as disciples require formation, transformed into the person of the Master, and share with His mission. The aim of this research to find the spirit of Jesus’ disciple and encourage their understanding of dimensions disciple. The method used in this research is the historical method. It relies primarily on library materials, Church documents, books, periodicals, and journals which are related to the study. The results of this investigation with its assumptions regarding institutional apostolates and its willingness to think of Christian existence as separable from sharing Jesus’ mission should be recast in the light of the New Testament discipleship. In order to renew the spirit of disciples is a need to examine the type of Jesus’s formation. The implication of this research to presents the biblical and theological foundation relationship with God, referred as disciples. The relation occurs throughout salvation history as manifestation of God’s love.